STRATEGI PENERJEMAHAN IDIOM DALAM BAB SATU NOVEL MARYAM KARYA OKKY MADASARI - Tjahyaningsih Tjahyaningsih; Umi Pujiyanti (JURNAL ILMIAH NUSANTARA, 2026)
This study analyzes idiom translation strategies and meaning equivalence in Chapter One of the novel Maryam by Okky Madasari and its English translation, The Outcast. The objectives of this study are to identify the types of idioms used, the translation strategies applied, and to assess the meaning equivalence between the source text and the target text. The method employed is descriptive qualitative with text analysis techniques. Data were collected by identifying idioms in the source text and its translation, then analyzed using Peter Newmark’s theory of idiom translation strategies and Eugene Nida’s theory of meaning equivalence. The findings show that three types of idioms were found: full idioms, partial idioms, and contextual figurative expressions. The most frequently used translation strategy was paraphrase, followed by direct idiomatic equivalence, adaptation, and omission. The paraphrase strategy was chosen because many idioms in Indonesian do not have direct equivalents in English. In terms of meaning equivalence, most idioms achieved dynamic equivalence, where the meaning and emotional effect were preserved even though the form of the idiom changed. However, some idioms experienced meaning shifts due to cultural differences between the source and target languages. This study concludes that translating idioms in literary works requires a balance between fidelity to the source text and readability in the target text. An understanding of cultural context is essential to maintaining naturalness and accuracy of meaning.